2023
DOI: 10.1039/d2bm01549h
|View full text |Cite
|
Sign up to set email alerts
|

Single-component lipid nanoparticles for engineering SOCS1 gene-silenced dendritic cells to boost tumor immunotherapy

Abstract: Dendritic cells (DCs) that can prime antitumor responses indicate a great potential in tumor immunotherapy, whereas the unsatisfactory effect which can be ascribed in part to the high expressions of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…DCs are the most common and typical APCs in the immune system, 51–54 and the antigen presentation and maturation of APCs is important in the activation of immune responses. 55 Thus, we analyzed the expression of biomarkers expressed on DCs after QS-21/Cryo cell and QS-21/UV-Cryo cell stimulation. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…DCs are the most common and typical APCs in the immune system, 51–54 and the antigen presentation and maturation of APCs is important in the activation of immune responses. 55 Thus, we analyzed the expression of biomarkers expressed on DCs after QS-21/Cryo cell and QS-21/UV-Cryo cell stimulation. According to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To accomplish desired therapeutic effects, efficient delivery of siRNA into cells is a prerequisite [31]. In this study, we chose OA2, a demonstrated effective cationic lipid nanoparticle with high transfection efficiency [32], as the carrier to deliver the siRNA against RAPSYN gene, which has shown excellent RAPSYN gene silencing in Ph + leukemia cell lines. In addition, OA2-siRAPSYN could significantly inhibit the proliferation of Ph + leukemia cell lines, through the regulation of Wnt/β-catenin/c-Myc signaling pathway, which is another advantage to possibly eliminate leukemia stem cells in Ph + leukemia patients [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…One interesting example of modulating SOCS1 levels, is the lipid nanoparticle (LNP) delivery of SOCS1-targeting small interfering RNA (siRNA) to bone marrow-derived DCs. Vaccination with OVA-specific DCs containing Socs1 siRNA prior to challenge with OVA-bearing B16F10 melanoma cells, successfully suppressed tumor growth through increased cytokine secretion and antigen presentation ( 182 ).…”
Section: Discussionmentioning
confidence: 99%